INCREASING THE ECONOMIC EFFICIENCY OF AGRICULTURAL PRODUCTS ON THE BASIS OF WORLD MARKET REQUIREMENTS (World Economics and Finance Bulletin, 2024)
This article provides information on the industrialization of the agricultural sector and the mechanism for the production of competitive and export products with high added value in the agricultural sector. This article discusses the development of a strategy for exporting agricultural products to international markets.
Keywords: Conditions of globalization; international market; competitive product; competitive advantage